Protandric Transcriptomes to Uncover Parts of the Crustacean Sex-Differentiation Puzzle - Levy, Tom; Zupo, Valerio; Mutalipassi, Mirko; Somma, Emanuele; Ruocco, Nadia; Costantini, Maria; Abehsera, Shai; Manor, Rivka; Chalifa-Caspi, Vered; Sagi, Amir; Aflalo, Eliahu D. (Frontiers in Marine Science, 2021)
Hermaphrodite systems offer unique opportunities to study sexual differentiation, due to their high degree of sexual plasticity and to the fact that, unlike gonochoristic systems, the process is not confined to an early developmental stage. In protandric shrimp species, such as Hippolyte inermis and Pandalus platyceros, male differentiation is followed by transformation to femaleness during adulthood. The mechanisms controlling sexual differentiation have not been fully elucidated in crustaceans, but a key role has been attributed to the insulin-like hormone (IAG) produced by the androgenic gland (AG), a crustacean masculine endocrine organ. To uncover further transcriptomic toolkit elements affecting the sexual differentiation of H. inermis, we constructed eye and whole body RNA libraries of four representative stages during its protandric life cycle (immature, male, young female and mature female). The body libraries contained transcripts related to the reproductive system, among others, while the eye libraries contained transcripts related to the X-organ-sinus gland, a central endocrine complex that regulates crustacean reproduction. Binary pattern analysis, performed to mine for genes expressed differentially between the different life stages, yielded 19,605 and 6,175 transcripts with a specific expression pattern in the eye and body, respectively. Prominent sexually biased transcriptomic patterns were recorded for the IAG and vitellogenin genes, representing, respectively, a key factor within the masculine IAG-switch, and a precursor of the yolk protein, typical of feminine reproductive states. These patterns enabled the discovery of novel putative protein-coding transcripts exhibiting sexually biased expression in the H. inermis body and eye transcriptomes of males and females. Homologs to the above novel genes have been found in other decapod crustaceans, and a comparative study, using previously constructed transcriptomic libraries of another protandric shrimp, P. platyceros, showed similar sexually biased results, supporting the notion that such genes, mined from the H. inermis transcriptome, may be universal factors related to reproduction and sexual differentiation and their control in other crustaceans. This study thus demonstrates the potential of transcriptomic studies in protandric species to uncover unexplored layers of the complex crustacean sex-differentiation puzzle.